DECISION SUPPORT SYSTEM FOR LECTURERS ACHIEVING USING ALGORITHM C.45 (STUDY: STIT PRINGSEWU LAMPUNG) - Fauzi Fauzi; Wulandari Wulandari; Muhammad Muslihudin (LPPM STMIK Pringsewu, 2020)
A lecturer is one of the essential components of a higher education system. Roles, duties, and responsibilities are very important in realizing national education, namely educating the nation's life, improving the quality of Indonesian people, which includes the quality of faith/piety, noble morals, and mastery of science, technology, and art, as well as realizing an advanced, fair, and advanced Indonesian society. prosperous, and civilized. Law Number 14 of 2005 concerning Teachers and Lecturers, 4 competencies must be possessed as a lecturer in carrying out the task of the Tridharma of Higher Education. The four competencies include pedagogic, professional, personality, and social. These four competencies are indicators that show the performance of lecturers as educators and teachers. In improving the quality of education at STIT Pringsewu, qualified lecturers are needed. The selection of outstanding lecturers will be one of the supporters in improving the quality at STIT Pringsewu. The algorithm C 4.5 method is one of the methods for making a decision tree based on the training data provided in determining the outstanding lecturers of STIT Pringsewu as many as 20 lecturers. From the results of data testing using the rapid manner tool, it was found that 4 people who got the criteria deserved an award as outstanding lecturers.